1999
DOI: 10.1029/1999gl900455
|View full text |Cite
|
Sign up to set email alerts
|

Sudden compression of the outer magnetosphere associated with an ionospheric mass ejection

Abstract: Abstract.On September 24, 1998 at 2345 UT the magnetosphere was suddenly compressed as the dynamic pressure of the solar wind rapidly rose from 2 to 15 nPa. At the Polar spacecraft, at high altitudes above the center of the northem polar cap, a remarkably smooth increase in the field strength occurred while the plasma properties changed abruptly, as described in an accompanying paper. Comparisons with models and an examination of the wave amplitudes during the compression indicate that the initial change in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…We instead propose another mechanism involving "preexisting" ions to explain the dynamic variation in the ionospheric outflow. The behavior of pre-existing outflow ions in the dynamics of the magnetosphere was mentioned qualitatively in previous studies [e.g., Russell et al, 1999;Peterson et al, 2009], but no supporting evidence has yet been provided.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…We instead propose another mechanism involving "preexisting" ions to explain the dynamic variation in the ionospheric outflow. The behavior of pre-existing outflow ions in the dynamics of the magnetosphere was mentioned qualitatively in previous studies [e.g., Russell et al, 1999;Peterson et al, 2009], but no supporting evidence has yet been provided.…”
Section: Introductionmentioning
confidence: 97%
“…However, using observations from the Polar spacecraft over the polar cap, Cladis et al [2000] showed an example where O + ions acquired their energies in a short time primarily through centrifugal acceleration in the shock event on 24 September 1998. During this event, which was also studied by Moore et al [1999], Russell et al [1999], and Strangeway et al [2000], the O + parallel velocity increased from 25 to 100 km/s in 2 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compression scenario has some support in simulations (e.g., Shue et al, 1997) and observations (e.g. Russell et al, 1999;Wilken et al, 1982, and references therein). Despite the opposite correlation of convection and density, the number flux also shows a positive correlation with dynamic pressure.…”
Section: Solar Wind Density and Dynamic Pressurementioning
confidence: 99%
“…Figure 1 shows an example of a large magnetospheric compression that occurred on September 24, 1998. This event was examined in various studies (e.g., Moore et al, 1999;Russell et al, 1999;Strangeway et al, 2000) which in particular put forward a rapid response of the ionosphere with enhanced outflows of low-energy plasma. The top panel of Fig.…”
Section: Introductionmentioning
confidence: 99%